“Losing access to outdoor spaces was the biggest challenge for children to be healthy”: pandemic restrictions and community supports for children’s movement in Nova Scotia - Locke, Maggie; Feicht, Becky; Stone, Michelle R.; Burke, Emily; Rehman, Laurene; Kirk, Sara F. L.; Faulkner, Guy; Moore, Sarah A. (Frontiers in Public Health, 2024)
Introduction Health-focused communities can promote physical activity for children by providing them with safe and supportive environments to move. Across the COVID-19 pandemic many community spaces and services were closed due to public health restrictions. During the pandemic, Atlantic Canada uniquely implemented an agreement between four provinces to restrict travel and reduce the spread of the virus. The “Atlantic bubble” led to fewer cases of COVID-19 and restrictions to community spaces and services. With restrictions now removed, community spaces and services likely play a critical role in facilitating the recalibration of children’s movement. Perspectives from families who experienced the “Atlantic bubble” may offer valuable insights to the use of these spaces during and after the removal of restrictions. Objective This study explored the role of community spaces and services on their child’s physical activity across the COVID-19 pandemic from the perspectives of Nova Scotia caregivers. Methods We employed a qualitative description approach and conducted semi-structured interviews with 14 caregivers of children aged 5–11 years who lived in Nova Scotia, Canada. Interviews were transcribed verbatim and analyzed using reflexive thematic analysis. Results Four themes were generated: (1) Public health restrictions limited community movement behaviors and social connections, (2) Spaces, locations, and environments influenced how families experienced physical activity during public health restrictions, (3) Virtual realities: screens supported a new sense of community for children throughout the pandemic, and (4) “Facilitated” and “forced adaptability”: public health restrictions changed family dynamics, routines, and movement behaviors. Conclusion Despite living in the “Atlantic bubble,” Nova Scotian caregivers shared that COVID-19 related public health restrictions shifted their family’s dynamics, routines, and ability to engage in physical activity within their communities. Community spaces and services can be leveraged to recalibrate children’s movement as pandemic-related restrictions are reduced. In future public health crises, community spaces and services should remain in place to whatever extent possible to reduce the collateral consequences of public health restrictions on children’s health.